1992
DOI: 10.1021/bi00127a023
|View full text |Cite
|
Sign up to set email alerts
|

Importance of aliphatic side-chain structure at positions 2 and 3 of the insulin A chain in insulin-receptor interactions

Abstract: In order to evaluate the cause of the greatly decreased receptor-binding potency of the naturally occurring mutant human insulin Insulin Wakayama ([LeuA3]insulin, 0.2% relative potency), we examined (by the semisynthesis of insulin analogues based on N alpha-PheB1,N epsilon-LysB29-bisacetyl-insulin) the importance of aliphatic side chain structure at positions A2 and A3 (Ile and Val, respectively) in directing the interaction of insulin with its receptor. Analogues bearing glycine, alanine, alpha-amino-n-butyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(138 citation statements)
references
References 47 publications
(72 reference statements)
8
124
1
Order By: Relevance
“…other hydrophilic residues (Table 3); 2) Nakagawa et al (4,14) reported We may ask why the insulin mutants where the conserved Val residues were replaced by Thr or Ile retained relatively high receptor-binding activities and in vivo biological potencies. By comparing the side-chains of Val, Thr, and Ile, it is seen that all the three residues contain a¯-branched side-chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…other hydrophilic residues (Table 3); 2) Nakagawa et al (4,14) reported We may ask why the insulin mutants where the conserved Val residues were replaced by Thr or Ile retained relatively high receptor-binding activities and in vivo biological potencies. By comparing the side-chains of Val, Thr, and Ile, it is seen that all the three residues contain a¯-branched side-chain.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not an absolute rule. There are some exceptions, for example, substitution of A2Ile in insulin by Thr caused a 1,000-fold decrease in receptor-binding activity whereas replacement by Leu caused only a 20-fold loss in activity (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, the single-chain insulin precursor has ϳ0.1% activity of the two-chain mature molecules (22). This has been interpreted that flexibility in the C terminus of the B-chain and a free N terminus of the A-chain are required for activity (22,23). The activity (lipogenesis) of the described single chain insulin aspart precursor featuring tryptophan in the C-peptide is further decreased 10-fold to ϳ0.01% of human insulin.…”
Section: Engineering-enhanced Eukaryotic Secretion 18246mentioning
confidence: 99%
“…The hexamers dissociate upon secretion into the portal circulation, enabling the hormone to function as a zinc-free monomer. Structure-function relationships have been inferred from patterns of sequence conservation (2) and extensively probed by mutagenesis (2)(3)(4)(5)(6)(7)(8)(9)(10). A variety of evidence suggests that insulin undergoes a change in conformation on binding to the insulin receptor (IR) 2 (11).…”
mentioning
confidence: 99%
“…4 Participation of His B5 in the R-specific ␣-helix ( Fig. 2, right, red circle) causes its side chain to move from the T 6 surface to pack within a trimer interface; the B5 side chain does not participate in zinc coordination or the immediate binding of phenol. The structural environment of His B5 within an R-specific trimer interface is shown in Fig.…”
mentioning
confidence: 99%